Sistem Pendukung Keputusan Rekomendasi Hotel Bintang Tiga Menggunakan Kombinasi Entropy dan Combine Compromise Solution - Wahyudi, Agung Deni; Sumanto, Sumanto; Setiawansyah, Setiawansyah; Yudhistira, Aditia (Graha Mitra Edukasi, 2024)
Three Star Hotels are lodging places that offer the perfect balance between comfort, adequate facilities, and affordable prices. With a friendly atmosphere and professional service, the hotel welcomes guests from various backgrounds warmly. One of the problems in choosing a Three Star Hotel is confusion due to variations in quality and facilities among hotels that have similar ratings. Although they share the same categories, the standards and services offered can vary greatly. This can make potential guests find it difficult to choose the right hotel that suits their preferences and needs. In addition, some hotels may not meet guest expectations due to issues such as poor cleanliness or facilities that do not function properly, which can generate dissatisfaction. The combination of Entropy weighting and the Combine Compromise Solution method can be a powerful approach in providing three-star hotel recommendations to potential guests. By combining these two methods, it can produce more informed and objective three-star hotel recommendations. Entropy weighting helps in assessing the relative importance of each criterion, while the Combine Compromise Solution allows us to reach a compromise solution that blends different preferences and criteria. The result is recommendations that are more accurate and tailored to potential guests' needs and preferences. The recommendation results showed that AN Hotel with a value of 1,782 got 1st place, AL Hotel with 1.271 got 2nd place, and YN Hotel with 1,145 got 3rd rank.